Unsafe sexual behavior of currently married men having sex with men in Thane, Maharashtra: a challenge for ensuring ZERO HIV transmission - Sakthivel, Saravanamurthy P.; Yadav, Awdesh; Tayyaba, Shaeik; Khambampatti, Rambabu; Mandal, Siddhartha; Agarwal, Ashok (International Journal Of Community Medicine And Public Health, 2018)
Background: Men having sex with men (MSM) in India due to social taboo and pressure, get married to women, and there is limited evidence on HIV-associated risk behaviors among MSM currently married (CM) to a female partner. The aims of the study was to analyse and understand HIV associated risk behaviors among MSM currently married to a female partner in Thane, Maharashtra. Methods: MSM accessing HIV prevention interventions through Targeted Interventions (TIs) in Thane, was approached through a cross-sectional study design. 67 CM-MSM and 57 never married (NM) MSM compared to understand the HIV associated risk behaviors. Engagement in vaginal intercourse, presently living with regular female partner and current marital status used as the screening variables. Statistical analysis used as descriptive, bi-variate and multi-variate analysis performed. Results: Mean age of the CM and NM-MSM together (N=124) is 30 years, with 31% as panthi self-identity, 28% double-decker and 18% bisexual. Unsafe anal sex with paid male/hijra, regular non-paying male and occasional non-paying male/hijra is significantly high among CM-MSM than NM-MSM. Conclusions: Targeted interventions (TIs) in Thane should ensure safe sex practices across all types of partners, especially among MSM married to women, and facilitating a conducive environment for MSM to decide their marital life.